High-precision geochronology links the Ferrar large igneous province with early-Jurassic ocean anoxia and biotic crisis - Burgess, Seth D; Bowring, Samuel A; Fleming, Thomas H; Elliot, David H (Earth and Planetary Science Letters, 2015)
Apparent synchrony between eruption/emplacement of large igneous province (LIP) magmas and mass extinction has led to the implication of magmatism as a primary trigger of global scale environmental change. Evaluating the efficacy of magmatism as a driver of global change depends on the relative timing of magmatism and environmental change, and the magma effusion/intrusion rate, both of which can be constrained by high-precision geochronology. Early Jurassic (Pliensbachian-Toarcian) global ocean anoxia and acidification, carbon isotope perturbations, and biotic crisis have been linked to "synchronous" eruption and emplacement of the Karoo and Ferrar LIPs. To better constrain the timing and duration of Ferrar magmatism, we apply the single crystal, chemical abrasion U-Pb ID-TIMS method to zircon crystals isolated from twenty Ferrar LIP sills and lavas, and the Dufek intrusion. Dates suggest that both intrusive and extrusive Ferrar magmatism occurred over an interval of 349. ±. 49 kyr, beginning with intrusive magmatism as early as 182.779. ±. 0.033 Ma. Lava eruption was synchronous with, and in some cases postdates intrusion. When coupled with existing geochronology on the Karoo province, our dates confirm broad synchrony between Karoo and Ferrar magmatism, though Karoo magmatism began demonstrably prior to Ferrar magmatism, starting as early as 183.246. ±. 0.045 Ma. The short-lived magmatic history of the Ferrar LIP makes it a plausible trigger for early-Jurassic environmental change. © 2015.
195 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/120-254-967-130-966 tex.type: [object Object]
Keywords: Anoxic events; Carbon isotopes; Chemical abrasions; Environmental change; Geochronology; Isotopes; Jurassic; Karoo; Large igneous province; Large igneous provinces; Lead; Mass extinction; Ocean anoxic event; Relative timing; Silicate minerals; Single crystals; South Africa; Uranium; Zircon crystals; dept.esc; emplacement; environmental change; geochronology; large igneous province; magmatism; mass extinction; paleoenvironment; peer-reviewed